2019
DOI: 10.1108/bfj-12-2018-0818
|View full text |Cite
|
Sign up to set email alerts
|

A sensory perspective in the Italian beer market

Abstract: Purpose From literature, an uncovered issue around the customer-based brand equity (CBBE) is detected: the influence of sensorial preferences on the relationship between social media communication and CBBE. The purpose of this paper is to investigate the effects produced by social media brand communication – both firm-created content (FCC) and user-generated content (UGC) – on CBBE, according to the sensorial preferences in the beer industry. Design/methodology/approach A literature review has been used to d… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
23
0

Year Published

2020
2020
2022
2022

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 15 publications
(23 citation statements)
references
References 66 publications
0
23
0
Order By: Relevance
“…In addition to this, there is a series of certifications, such as protected denomination of origin and protected geographical indication, which guarantee the origin of the product (Bandinelli et al, 2020;Rossi et al, 2014). As a result, farms have become competitive in international markets and have undergone a metamorphosis in their production cycle, leaving behind traditional ways of production (Backer et al, 2009;Bresciani et al, 2013;Sadeghi et al, 2019a, b;Cillo et al, 2019a).…”
Section: Introductionmentioning
confidence: 99%
“…In addition to this, there is a series of certifications, such as protected denomination of origin and protected geographical indication, which guarantee the origin of the product (Bandinelli et al, 2020;Rossi et al, 2014). As a result, farms have become competitive in international markets and have undergone a metamorphosis in their production cycle, leaving behind traditional ways of production (Backer et al, 2009;Bresciani et al, 2013;Sadeghi et al, 2019a, b;Cillo et al, 2019a).…”
Section: Introductionmentioning
confidence: 99%
“…According to the CAOS model (Paoloni, 2011) showing the relationships between parties, the strongest relationship is between variables S and A—the informal and permanent relationships (Cavicchi and Vagnoni, 2018; Inkinen, 2016). Other relationships outlined in the body of the paper, between variables S and C and between S and O (Cillo et al , 2019; Scuotto et al , 2017; Scuotto et al , 2017), are characterized by relationships subsequent and consequent to the informal and permanent relationship (Al Saifi, 2015; McIver and Wang, 2016) between variables S and A—the territory (the company and Regione Sardegna) and its local product (Pecorino Cheese).…”
Section: Discussionmentioning
confidence: 99%
“…The relations (Cillo et al , 2019; Scuotto et al , 2017) are important in order to understand how the networks support the enterprise in developing a business.…”
Section: Methodsmentioning
confidence: 99%
“…In one study, a stronger sense of community with their online brand community was indirectly related to loyalty through key variables such as trust (Laroche et al, 2013). In another study, researchers found that beer enthusiasts who evaluated user-generated social media communication more positively also showed greater brand loyalty (Cillo et al, 2019). Similarly, Salgado and Vela (2019) found that loyalty among students could be increased through more engagement in their virtual community with their university via a "brand fan page.…”
Section: Sense Of Community and Brand Loyaltymentioning
confidence: 99%